The Colonizer Abroad - McBride, Christopher (Literary Criticism and Cultural Theory, 2004)
Looking at a diverse series of authors--Herman Melville, Richard Henry Dana, Jr., Mark Twain, Charles Warren Stoddard, and Jack London--"The Colonizer Abroad" claims that as the U.S. emerged as a colonial power in the nineteenth and twentieth centuries, the literature of the sea became a literature of imperialism. This book applies postcolonial theory to the travel writing of some of America's best-known authors, revealing the ways in which America's travel fiction and nonfiction have both reflected and shaped society.